Formula development and characterization of nanostructured lipid carriers (NLC) vitamin E acetate with solid lipids compritol and precirol - Salsabilla, Syifa; Jafar, Garnadi; Fatmawati, Fenti (Science Midwifery, 2024)
Vitamin E acetate has antioxidant activity that can prevent premature aging of the skin, but its nature is very lipophilic (log p±12.2) and has the potential to degrade. To overcome the problems of permeability and stability, vitamin E acetate needs to be developed in Nanostructured Lipid Carrier (NLC), which is a nano delivery system based on solid lipids and liquid lipids stabilized by surfactants as a colloidal system. The formulation of vitamin E acetate into NLC was carried out using the heat homogenization method, then sonicated using a probe sonicator. The materials used were 2% vitamin E acetate, 2-6% Compritol® and Precirol® solid lipids, 1% Myritol®, and 1-3% Chremophore and Plantacare® surfactants. The NLC results were then characterized by measuring particle size, zeta potential, polydispersity index, entrapment efficiency, and morphology. The characterization results showed that NLC vitamin E acetate had a particle size of 280-375 nm, a zeta potential of -23 mV to -28 mV, a polydispersity index <0.5, an entrapment efficiency of 92-97%, and a spherical morphology. The results showed that Nanostructured Lipid Carrier vitamin E acetate gave good results.